2008
DOI: 10.1080/13651820701883155
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic evaluation of cystic pancreatic lesions

Abstract: The diagnosis of CPN remains challenging. Cross-sectional imaging methods do not reliably give an accurate preoperative diagnosis. Surgeons should continue to err on the side of resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 47 publications
1
35
0
1
Order By: Relevance
“…The other question is the nature of the lesion and whether it is benign or malignant. Taking careful clinical history and using the imaging modalities and biochemical markers described below could be helpful to establish a preoperative diagnosis although making a definitive preoperative diagnosis may still not be possible [22]. Caution should be exercised when interpreting the clinical and radiological findings.…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…The other question is the nature of the lesion and whether it is benign or malignant. Taking careful clinical history and using the imaging modalities and biochemical markers described below could be helpful to establish a preoperative diagnosis although making a definitive preoperative diagnosis may still not be possible [22]. Caution should be exercised when interpreting the clinical and radiological findings.…”
Section: Diagnosismentioning
confidence: 99%
“…Caution should be exercised when interpreting the clinical and radiological findings. In particular, clinical history of pancreatitis and hyperamylasaemia should be interpreted with caution as IPMN can present with acute pancreatitis by compression of the pancreatic duct or occlusion of the pancreatic secretion [22] [23]. Indeed, mucinous cystadenoma with histologically proved ovarian like stroma has been reported to present with acute pancreatitis [24].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…This could be explained by a diagnostic superiority of MRI. However, previous studies showed that CT and MRI have an equal diagnostic accuracy for the characterization of CPTs [22,25]. Other authors rate MRI as more specific than CT due to a better depiction of septae and cyst contents as well as the pancreatic duct, especially with the use of MRCP [4, 26 -30].…”
mentioning
confidence: 99%